The adventures of Super Diaper Baby : the first graphic novel - Pilkey, Dav, 1966-; Pilkey, Dav, 1966- (Graphix, an imprint of Scholastic, 2025)
"Super Diaper Baby is an actual baby called Billy who gains special superpowers along with his trusty companion, Diaper Dog. Our dynamic superhero's archenemy, Deputy Dangerous, wants to steal his powers and take over the planet. Will the diaper-wearing dynamo duo defeat the deputy, or is the entire Earth doomed? Bonus content includes How 2 Draws and a look behind the scenes at the creation of The Adventures of Super Diaper Baby, featuring pages from Dav Pilkey's sketchbook and more! With a special appearance by Captain Underpants, The Adventures of Super Diaper Baby is the hilarious graphic novel tale of a superhero who's faster than a speeding stroller and more powerful than diaper rash." --